Поделки из фольги - Плотникова Татьяна Федоровна (Для дома, для семьи, 2012)
Экземпляры: ЦБ (20170206) / Инвентарный номер: 53418 / Цена: 100.00 / Сис.шифр: 85.125 / Авт.знак: П 39 / ГРНТИ: 18 / ББК: 85.125